TIPE KEPRIBADIAN MELALUI MYERS BRIGGS TYPE INDICATOR DENGAN KINERJA PERAWAT DI RUANG RAWAT INAP RSUD TARAKAN JAKARTA - Fida Nabilah Auliya, (2023)
In maintaining and improving the quality of hospital services is determined by the quality of nurse performance. Nurse performance is influenced by several factors, one of which is psychological factors, namely personality between individuals. However, the results of psychological tests based on MBTI (Myers Briggs Type Indicator) personality types with nurses are still rarely found. This study aims to explore the MBTI personality type on nurse performance. This research method uses quantitative with a comparative approach. Sampling using purposive sampling as many as 230 respondents. Data were analyzed with the Non Parametric Kruskall Wallis Test and the results of the study obtained a p value of 0.198> 0.05 (Sig 95%) meaning that there is no significant difference between the nurse's MBTI personality type and nurse performance at the Jakarta Tarakan Hospital. The results of the study found that there were only 14 personality types and no ENTP and ENFP personality types were found in nurses at RSUD Tarakan. And it was found that the highest performance value was found in the INTP personality type (193.50) and the lowest INFJ (65.75). It is recommended that the hospital continue to develop the personality of the nurses to maintain inter-team relationships so as to form a superior nursing staff and create good nursing management.